Pengembangan Model Project-Based Learning Berbasis Pembuatan Film untuk Meningkatkan Literasi Mahasiswa pada Mata Kuliah Bahasa Indonesia Keilmuan - Mokalu, Yohanes Bery; Paat, Meike; Polii, Intama Jemy; Akbar, Jakub Saddam; Kuron, Meidy Atina (LPPM Politeknik Saint Paul Sorong, 2024)
This study aims to develop a filmmaking-based Project-Based Learning (PjBL) model for the Scientific Indonesian Language course to enhance the literacy skills of Science Education students. The model aims to integrate scientific literacy, including reading, writing, and critical thinking, with creative communication through the production of short films. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this research follows a research and development (R&D) approach. The findings reveal that the model significantly improves students' literacy abilities, with an average increase of 26% in post-implementation test scores. Moreover, the filmmaking process encourages students to better understand complex scientific concepts and fosters creativity, collaboration, and problem-solving skills. Reflections on the films provide opportunities for students to evaluate their learning outcomes and refine their skills. This PjBL model demonstrates effectiveness in supporting interdisciplinary learning and is recommended for broader application in similar academic contexts to enhance student literacy and engagement.